The new triad power: impact on global markets, resources and politics - Sheth, Jagdish N. (Henry Stewart Talks, 2014)
The fundamental shift in global growth, Forces driving the shift- Aging of affluent nations and economic reforms, Rise of the new middle class, Economic growth engines for the world, New measures of world economies, China versus India beyond 2020, Chindia rising, The old and new triad power, Impact on global markets, Emergence of largest consumer markets, Rise of Chindia’s global enterprises, Fusion of cultures (music, food & spirituality), Private equity in emerging markets, Impact on global resources, Resource driven global expansion and mergers, Emergence of strange bedfellows, China in Africa, Rise of scarcity driven profits, Sustainability imperative, Impact on global politics, Economics as driver of politics, G-8 becomes G-20, Rise of multilateral politics, Growth of Asian sovereign funds, Multiple currency reserves, Redefining capitalism & democracy